Field- and Lab-Based Potentiometric Titrations of Microbial Mats from the Fairmont Hot Spring, Canada. Issue 10 (26th November 2017) - Warchola, Tyler J.; Flynn, Shannon L.; Robbins, Leslie J.; Liu, Yuxia; Gauger, Tina; Kovalchuk, Olga; Alam, Md. Samrat; Wei, Siwen; Myers, Reed; Bishop, Brendan; Lalonde, Stefan V.; Gingras, Murray K.; et al.
ABSTRACT: Potentiometric titrations are an effective tool to constrain the protonation constants and site concentrations for microbial surface ligands. Protonation models developed from these experiments are often coupled with data from metal adsorption experiments to calculate microbial ligand-metal binding constants. Ultimately, the resulting surface complexation models can be used to predict metal immobilization behavior across diverse chemical conditions. However, most protonation and metal-ligand thermodynamic constants have been generated in laboratory experiments that use cultured microbes which may differ in their chemical reactivity from environmental samples. In this study, we investigate the use of in situ field potentiometric titrations of microbial mats at a carbonate hot spring located at Fairmont Hot Springs, British Columbia, with the aim to study microbial reactivities in a natural field system. We found that authigenic carbonate minerals complicated the potentiometric titration process due to a "carbonate spike" introduced by the contribution of inorganic carbonate mineral dissolution and subsequent carbonate speciation changes during the transition from low to high pH. This inhibits the determination of microbial surface ligand variety and concentrations. Our preliminary study also highlights the need for developing novel probes to quantify in situ microbial mat reactivity in future field investigations.